Exploring the relative contributions of training patterns and training contexts to burnout and dropout in swimming - Larson, H. K. (University of Alberta, 2019)
Millions of children participate in youth sport, which has been associated with both potential benefits and harms. The promotion of positive, beneficial experiences in youth sport and the reduction of harmful, negative experiences requires discerning those factors which could be decisive in a positive or negative direction. The purpose of this dissertation was to better understand the relative contributions of training patterns (specifically, training volume and early specialization) and training contexts (i.e., the social environment) to burnout, dropout, and lifelong enjoyment of sport, specifically within the sport of swimming. Specific aims were to (i) advance the assessment of early sport specialization in alignment with its most recently established definition, (ii) examine the relationships that early specialization indicators and training volume have with burnout and dropout in swimming, (iii) explore theoretical models of these relationships, including psychosocial variables from the sport commitment model and self-determination theory, and (iv) explore the influence of youth swimming experiences—including training patterns and training contexts—on transitions to adult swimming participation. These first three aims necessitated surveys with youth swimming participants and their parents. Swimmers self-reported ratings on various psychological variables and their parents detailed the swimmers` sport backgrounds. Chapter 2 outlines the relationships of various markers of early specialization with each other, and with burnout and dropout. The early specialization items were not related to burnout or dropout in the expected directions. Several possible explanations for this finding are presented, including a motivational explanation. Chapter 3 continues this exploration, focusing on the relative contributions of training volume and training context (represented by perceptions of autonomy support) to burnout and dropout. Structural equation modelling was used to test a commitment model of burnout. Compared to training volume, autonomy support emerged as a much stronger predictor of enjoyment, burnout, and intentions to continue swimming. The fourth aim was achieved by conducting interviews with twenty masters (adult) swimmers with previous youth swimming experience, discussed in Chapter 4. Some of these participants (labelled as "continuers") transitioned directly from youth swimming into masters swimming. Others (labelled as "rekindlers") had a break, sometimes lasting several years, between ending their youth swimming participation and returning to the sport as masters athletes. High training volume in youth swimming appeared to have both negative and positive consequences that influenced subsequent transitions to adult swimming. Findings suggested that the youth training context created by coaches and peers had a strong influence on how participants perceived their training volume. The findings from this dissertation suggest that early specialization and high volumes of training in and of themselves do not increase the risk of burnout, dropout, and decreased adult sport participation. Rather, the context in which training takes place is a much stronger determinant of whether or not these negative outcomes will occur. If athletes` psychological needs are met and not thwarted, and if they are experiencing enjoyment and functional commitment, the risk of burnout and dropout is likely low, regardless of their level of specialization or training volume.